Elevated carbon monoxide observations over the North Pacific upper troposphere (July 2012–February 2013) - Kuo-Ying Wang; Philippe Nedelec; Valerie Thouret; Hannah Clark; Andreas Wahner; Andreas Petzold (PLoS ONE, 2025)
A novel use of routine, commercial, and regular in-service passenger airplane in collecting chemistry data over the North Pacific upper troposphere for climate research was started in July 2012. The European In-Service Aircraft for a Global Observing System (IAGOS) Package-1 was installed aboard a commercial Airbus A340-300 (B18806) operated by China Airlines (CAL). In this work we present carbon monoxide (CO) collected during the period from July 2012 to February 2013. Our findings, when compared with NASA aircraft missions in 1991, 1994, and 2001, indicate increase in anthropogenic CO pollution in the North Pacific upper troposphere from 1991 to 2012. Elevated CO concentrations (>160 ppbv) were prominent in the summer months of July and August, followed by September, while concentrations were lower (<100 ppbv) from October 2012 to February 2013. The results underscore effective vertical transport of ground-level anthropogenic pollutants to the upper troposphere. HYSPLIT model calculations affirm that Asian industrial regions at ground level are the primary sources of CO pollution in the downwind areas of the North Pacific upper troposphere. This study enhances our understanding of temporal variations and sources of CO pollution in this specific region, utilizing routine in-situ measurements on commercial aircraft to contribute valuable insights to air quality and pollution transport dynamics.